Effect of temporal changes and plantation age on gas exchange characteristics of Populus deltoides in the Indo-Gangetic plains of India - Kumar, Parveen; Singh, Kailash; Mishra, Ajay Kumar; Kumar, Ashwani; Singh, Rakesh; Rai, Poornima; Chaudhari, S.K.; Sharma, D.K. (Indian Journal of Agroforestry, 2020)
Temporal changes and plantation age have potential impact on gas exchange characteristics and soil respiration in Populus deltoides plantation, which is inferred in the present study. Temporal changes indicated statistically significant variation for gas exchange parameters and soil respiration. Plantation age showed decline trend in gas exchange parameters viz. net photosynthetic rate (Pn), transpiration (E), stomatal conductance (gs), intercellular CO2 concentration (Ci) concentration and water use efficiency (WUE). Whereas, soil respiration (SR) increased with plantation age. During the early rainy season (May), poplar trees showed lowest Pn (8.06 ìmol CO2 m-2 s-1), while at the end of the rainy season (September) poplar showed highest Pn of 20.45 ìmol CO2 m-2 s-1, whereas, the same plant showed 18.03 ìmol CO2 m-2 s-1 Pn during the early dry season (January). Significant and positive correlation was also observed between Pn and E (r = 0.803**), Ci and SR (r = 0.819**), gS and PAR (r = 0.753**), which reflected that these gas exchange attributes were correlated. Due to short rotation plantations, fast growth rate and adaptability to a range of environments, physiological and soil related parameters under Populus deltoides were significantly influenced by the temporal and plantation age changes which directly influenced the growth, biomass and ultimately the carbon sequestration.